(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the inclusion of mental skills in the content of the mathematics book for the first intermediate grade in the Republic of Iraq for the academic year 20212-022.The researcher used the descriptive analytical method in order to fit the objectives of the research, as the research sample consisted of the content of the mathematics book for the first intermediate grade, and the idea unit, which may be explicit or implicit as a unit for recording or repetition as a unit for counting, was adopted.After presenting the list to a number of specialists with expertise and specialization in teaching methods, the list obtained an agreement of more than (93%) of the arbitrators’ opinions. The mathematics book for the first intermediate class was analyzed according to mental skills in two ways: the researcher with himself and the researcher with an external analyst and using the Holsti equation. The following results were obtained: The mathematics book for the first intermediate grade obtained (725) recurrences and a percentage (100%) of the mental skills mentioned in the book. Where the main organizing skill got the highest frequency than the rest of the other main skills. The sub-comparison skill was less frequent than the rest of the other sub-skills.I neglected my skill in formulating questions and the skill in identifying main ideas, as I did not get any repetitions mentioned.